2013
DOI: 10.1021/mp400359w
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle Integrated Transdermal Patch for Fast Onset and Sustained Delivery of Lidocaine

Abstract: Lidocaine as an analgesic is of particular interest in both acute and chronic pain conditions and is used via injections or transdermal patches. While injections are associated with problems such as patient incompliance, topical administration of lidocaine using patches is less efficient due to variability of drug absorption among individuals, slower drug permeation through the skin, and hence a resultant undesirable delay in analgesic effects. To address this clinical problem, we developed a microneedle integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 31 publications
(71 reference statements)
1
37
0
Order By: Relevance
“…Research has shown significant increases in skin permeability using optimized MNs when considering factors of MN length, number of MNs, the length and width aspect ratio and surface area (Al-Qallaf & Das, 2008Olatunji et al, 2012Olatunji et al, , 2013Guo et al, 2013). It has been suggested that MNs can be adapted to aid lidocaine delivery yielding many fold increase in delivery rate (Kwon, 2004;Li et al, 2008;Wilson et al, 2008;Zhang et al, 2012a, b;Kochhar et al, 2013;Ito et al, 2013;Nayak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown significant increases in skin permeability using optimized MNs when considering factors of MN length, number of MNs, the length and width aspect ratio and surface area (Al-Qallaf & Das, 2008Olatunji et al, 2012Olatunji et al, , 2013Guo et al, 2013). It has been suggested that MNs can be adapted to aid lidocaine delivery yielding many fold increase in delivery rate (Kwon, 2004;Li et al, 2008;Wilson et al, 2008;Zhang et al, 2012a, b;Kochhar et al, 2013;Ito et al, 2013;Nayak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, it can be used as a combination of the delivery system and device, as the therapeutic compounds may be encapsulated (by mixing or solubilizing in prepolymer solution) during the fabrication of MNs. 5,6,17 The solubility of the added compound inside the prepolymer solution should be taken into consideration as the MN characteristics, e.g., MN strength, may change.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Coated [28] , encapsulated [29] , and dissolving [31] microneedles all provide novel drug delivery systems that can potentially facilitate increased levels of anaesthetic permeation. Nayak et al [26] have also used a novel topical lidocaine formulation in combination with microneedles to accelerate anaesthetic permeation.…”
Section: Predicting Tetracaine Onset Timementioning
confidence: 99%
“…Previous studies have shown that microneedles can improve the permeation of lidocaine into the skin. These studies used microneedles to either (i) pre-treat skin before the topical application of a lidocaine hydrochloride solution [25] or hydrogel formulation [26,27] , (ii) deliver lidocaine from a dry-coated microneedle surface [28] , or (iii) encapsulate lidocaine within a microneedle patch [29] . The formulations used in these studies are currently not clinically approved for human use.…”
mentioning
confidence: 99%